The Rise of the Creative Class: And How It's Transforming Work, Leisure, Community and Everyday Life - Tufts, Steven (Just Labour: A Canadian Journal of Work and Society, 2003)
The Rise of the Creative Class: And How It's Transforming Work, Leisure, Community and Everyday Life, by Richard Florida, is reviewed.